2014
DOI: 10.9734/bmrj/2014/6386
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Antibacterial Effect of Mouth Washes and Vernonia amygdalina (del.) on Some Tooth Decay Causing Bacteria

Abstract: Aims: To determine the antibacterial effect of the ethanol stem extract of Vernonia amygdalina (bitter-leaf) and some mouth washes against some bacteria that have been implicated in causing tooth decay so as to establish the role of herbal medicine and chemical compounds in oral hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Several studies carried out on this plant had suggested that it contains different bioactive compounds, including, flavonoids, saponins, alkaloids, tannins, phenolics, terpenes, steroidal glycosides, triterpenoids, and several types of sesquiterpene lactones (Erasto et al, 2006;Farombi and Owoeye, 2011;Kiplimo et al, 2011;Toyang and Verpoorte, 2013;Adedapo et al, 2014;Quasie et al, 2016;Luo et al, 2017). These bioactive compounds made them possess different pharmacological properties like antimicrobial, antimalarial, antithrombotic, antioxidant, anti-diabetic, laxative, hypoglycemic, antihelmintic, anti-inflammatory, cathartic, anticancer, antifertility, anti-fungi, antibacterial, and among others (Igile et al, 1994;Akinpelu, 1999;Iwalokun et al, 2006;Erasto et al, 2007;Gresham et al, 2008;Khalafalla et al, 2009;Ilondu, 2010;Farombi and Owoeye, 2011;Anibijuwon et al, 2012;Ngatu et al, 2012;Adetunji et al, 2013;Atangwho et al, 2013;Akinyele et al, 2014;Ezeadila et al, 2015;Udochukwu et al, 2015;Alara et al, 2017c). The objective of this review paper is to outline and discuss the studies that had been done on the bioactive compounds, phytochemical and pharmacological properties of V. amygdalina.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out on this plant had suggested that it contains different bioactive compounds, including, flavonoids, saponins, alkaloids, tannins, phenolics, terpenes, steroidal glycosides, triterpenoids, and several types of sesquiterpene lactones (Erasto et al, 2006;Farombi and Owoeye, 2011;Kiplimo et al, 2011;Toyang and Verpoorte, 2013;Adedapo et al, 2014;Quasie et al, 2016;Luo et al, 2017). These bioactive compounds made them possess different pharmacological properties like antimicrobial, antimalarial, antithrombotic, antioxidant, anti-diabetic, laxative, hypoglycemic, antihelmintic, anti-inflammatory, cathartic, anticancer, antifertility, anti-fungi, antibacterial, and among others (Igile et al, 1994;Akinpelu, 1999;Iwalokun et al, 2006;Erasto et al, 2007;Gresham et al, 2008;Khalafalla et al, 2009;Ilondu, 2010;Farombi and Owoeye, 2011;Anibijuwon et al, 2012;Ngatu et al, 2012;Adetunji et al, 2013;Atangwho et al, 2013;Akinyele et al, 2014;Ezeadila et al, 2015;Udochukwu et al, 2015;Alara et al, 2017c). The objective of this review paper is to outline and discuss the studies that had been done on the bioactive compounds, phytochemical and pharmacological properties of V. amygdalina.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections caused by multiple antibiotic resistant (MAR) bacteria are a growing threat worldwide [2]. Plants have the major advantage of still being the most effective and cheaper alternative source of drugs [3]. Vernonia amygdalina, a member of the Asteraceae family, is a small ever green shrub that grows in tropical Africa [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are also lactobasillus organisms that plays a role in the formation of dental caries. [5] Streptococcus plays a role in the early stages of caries by destroying the outer part of the enamel, meanwhile lactobasillus will be taking over the role of deep caries. 4 According to RISKESDAS in 2013, DMF-T scores in Indonesia is 4.6.…”
Section: Introductionmentioning
confidence: 99%
“…The catechins contained in the tea leaves are composed of several compounds: C (catechin), EC (epicatechin), EGC (epigalocatechin), and ECG (epigalocatechin). [5] Catechins contained in tea leaves are bactericidal and bacteriostatic. Catechin works by destroying the cytoplasmic membrane of the bacteria as well as causing protein denaturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation